Activation of Astrocytes in the Persistence of Post-hypoxic Respiratory Augmentation - Fukushi, Isato; Takeda, Kotaro; Pokorski, Mieczyslaw; Kono, Yosuke; Yoshizawa, Masashi; Hasebe, Yohei; Nakao, Akito; Mori, Yasuo; Onimaru, Hiroshi; Okada, Yasumasa (Frontiers in Physiology, 2021)
Acute hypoxia increases ventilation. After cessation of hypoxia loading, ventilation decreases but remains above the pre-exposure baseline level for a time. However, the mechanism of this post-hypoxic persistent respiratory augmentation (PHRA), which is a short-term potentiation of breathing, has not been elucidated. We aimed to test the hypothesis that astrocytes are involved in PHRA. To this end, we investigated hypoxic ventilatory responses by whole-body plethysmography in unanesthetized adult mice. The animals breathed room air, hypoxic gas mixture (7% O2, 93% N2) for 2 min, and again room air for 10 min before and after i.p. administration of low (100 mg/kg) and high (300 mg/kg) doses of arundic acid (AA), an astrocyte inhibitor. AA suppressed PHRA, with the high dose decreasing ventilation below the pre-hypoxic level. Further, we investigated the role of the astrocytic TRPA1 channel, a putative ventilatory hypoxia sensor, in PHRA using astrocyte-specific Trpa1 knockout (asTrpa1-/-) and floxed Trpa1 (Trpa1 f/f) mice. In both Trpa1f/f and asTrpa1-/- mice, PHRA was noticeable, indicating that the astrocyte TRPA1 channel was not directly involved in PHRA. Taken together, these results indicate that astrocytes mediate the PHRA by mechanisms other than TRPA1 channels that are engaged in hypoxia sensing.